(3GdEfSGf GdcGed aj eYQaI GdChGNQ hGdChGFds - (3YHO GdcQje Hf EHQGgje Hf YHO GdcQje GdLjdj GdUhaj , bWH GdOjf,J (B832 (3g` s
(3ChdgG (B:s
(3GdMeO ddg def bGe HMeOg GSe Gddg s
(3BNQgG (B:s
(3GdHGH GdKGef YTQ aj GdEQGOI s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B50 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B313s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B181s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
(3GdfSNI eHJhQI GdBNQ s
Keywords: (3GdJUha hGdBOGH GdTQYjIs